The Chinese Cultural Revolution Database. - Schoenhals, Michael (China Quarterly, 2003)
A review of The Chinese Cultural Revolution Database, a CD-ROM with hard copy indexes in English and Chinese, is provided. The writer recommends that all research libraries should purchase a copy of this CD-ROM, because it is certain to remain an invaluable resource for historians, political scientists, linguists, economists, sociologists, and journalists who are interested in Chinese issues.